Efficacy of Forestry Conservation Policy on Rural Livelihoods in Uganda: Evidence from Mabira Forest Reserve - Agea, Jacob G.; Obua, Joseph; Fungo, Bernard (Medwell Publishing, 2009)
A study was conducted from 2005-2007 in areas around Mabira Forest Reserve, Central Uganda. The objectives were to assess: awareness of the local communities about the current Forest Policy in Uganda, the local communities’ opinions about the efficacy of the current Forest Policy, and the capacity in terms of training to manage forest resources by local communities. Fifty-two households from 4 villages were interviewed in Najjembe sub-county in Mukono district that surrounding Mabira Forest Reserve. Questions were pre-determined and interviews guided. Individuals were interviewed for about 30-60 min. Primary data were subjected to content analysis, coded and subsequently analysed using Statistical Package for Social Scientist (SPSS). About 78% of the respondents were aware of the current Forest Policy in Uganda. About 59% of the respondents said that utilization and socio-economic benefits is strongly supported by the Forest Policy. Half of the respondents disagree that local people have more access to forest products than before under the current Forest Policy. About the same number of the respondents disagree that the forest and tree cover has increased under the present Forest Policy. Capacity to manage forest resources by local communities was weak, majority of the respondents said that none of their household members had received any of training in natural and or plantation forest management. Many institutions including National Forestry Authority (NFA), National Environment Management Authority, Uganda Wildlife Authority (UWA), Local Governments and Civil Society Organizations were reportedly playing key roles in conservation and management of the forest. There is a need for campaigns in order to realign policies that allows for full participation of not only the government but also the local communities in forest conservation and management.
Keywords: Forest policy; rural livelihoods; conservation; management; Uganda